The Study of Parts of Speech in the Lessons of the Russian Language in Primary Grades - Rizoqulovna, Nosirova Dilnoza (European Journal of Life Safety and Stability (2660-9630), 2021)
The article is devoted to the study of parts of speech in primary grades and the methods used to explain the topic "Parts of speech" on Russian lessons.